Auf neuen sprachwegen? : Rezeptions- und literaturkritische problematik anhand eines textes aus der deutschen immigrationsliteratur - Van Ryneveld, Hannelore Elisabeth (German Language and Literature, 2016)
The emerging body of literature defined in German literary circles as Auslӓnderliteratur or during the seventies as Gastarbeiterliteratur, forms the field of this research. The authors are foreigners living in Germany who write in Germanbut for whom German is not their mother-tongue. This dissertation uses the definition"deutsche lmmigrationsliteratur'', with the understanding that an attempt to define a body of literature is inherently problematical and lends itself too easily to categorisation and prejudices. This, in terms of current thinking within the minority discourse, perpetuates "colonialism" within the context of language and literature.(What is meant by prejudices in this context is the thinking that these writings are primarily ethnographic documents with the obligatory exotic flavour, and therefore not to be taken seriously as literary texts. The historical analysis of the dissertation however shows, that while the lmmigrationsliteratur might have begun like that, it has moved quite a long way from that point.)The issues which the first part of the research wishes to address are as follows: What is meant by the. definition deutsche lmmigrationsliteratur: what are the historical perspectives and what is its current status in terms of, on the one hand, mainstream German literature and on the other hand, minority discourse. Why does this body of literature appear to be marginalised by German literary critics? Is the marginalisation linked to an unwillingness to take literature written by foreigners in German seriously, or is it as a result of a reluctance to confront the innovative and at times provocative use of the German language? Does this literature differ aesthetically from the mainstream German literature? The existence of a body of aesthetics is an area which to date has not been extensively researched nor documented, with the exception of work done mainly by AMODEO(1996), but also GRONEFELD (1996) and CHIELLINO (1995).